A Comparative Study of Indoor Pavements Waste Generation During Construction through Simulation Tool. Issue 1 (June 2016) - Saldaña-Márquez, J.M.;; Gámez-García, H.;; Gómez-Soberón, D.C.;; Arredondo-Rea, M.C.;; Corral-Higuera, S.P.;; R, R
No abstract available